In silico investigations revealed four potential colon cancer drugs from phytochemicals in Zingiber officinale - Fortunatus Chidolue Ezebuo; Colin B Lukong; Ikemefuna C Uzochukwu; Irene N Okafor (International Journal of Phytomedicine, 2016)
Cancer is a difficult disease to treat, and few effective drugs are available. Hence, it is of great importance to develop effective anti-cancer therapeutic agents with well-defined pharmacokinetic properties. Although, ginger (Zingiber officinale) has a number of proven pharmacological activities, its effect on colon cancer has not received much attention. This study therefore investigated the potential colon cancer drug of compounds found in ginger. Dihydropyrimidine dehydrogenase was modeled using comparative homology modeling and virtual screening was performed locally on a Linux platform using AutoDock Vina®. The results showed that human dihydropyrimidine dehydrogenase is a homolog of pig dihydropyrimidine dehydrogenase. The leads of potential colon cancer drugs were beta-sitosterol, 6-Shogoal, Alloaromadedrene, and Zingiberol. They had similar binding site with levamisole for tumor necrosis factor ligand superfamily member 6 with His 148 and Tyr 192 common at their binding site whereas they had different binding sites from 5-fluorouracil for dihydropyrimidine dehydrogenase. The leads had better bioactivities compared with reference drugs (5-flourouracil and Levamisole) approved clinically for the treatment of colon cancer. In vitro, ex vivo and/or in vivo validations of the leads against colon cancer are recommended.